SATOLEP: Narratives of a city in the contrary way - Cristiano Guedes Pinheiro, Denise Marcos Bussoletti, Daniela da Cruz Schneider
This article presents and discusses the concepts of narrative and city "in the contrary way". The concepts originated from researches and actions undertaken by NALS (Núcleo de Arte, Linguagem e Subjetividade), center linked at Faculdade de Educação, at Universidade Federal de Pelotas. Considering the city of Pelotas (or Satolep) as stage, we present accounts of two masters grios linked of the city's black movement, from which the concepts underlying this work are developed. After that, the milestones of a pedagogy in the contrary way or pedagogy of the borderwill be outlined. In the end, for a not defined conclusion, questions that composed the research will be proposed.